The hero two doors down : based on the true story of friendship between a boy and a baseball legend - Robinson, Sharon, 1950- (New York : Scholastic Press, 2016)
Eight-year-old Steve Satlow is thrilled when Jackie Robinson moves into his Jewish neighborhood in Brooklyn in 1948, although many of his neighbors are not, and when Steve actually meets his hero he is even more excited--and worried that a misunderstanding over a Christmas tree could damage his new friendship.
School Library Journal, January 2016.
Publisher's Weekly, October 2015.
Teacher Librarian, February 2017.
Kirkus Review, November 2015.
3.9
3-6
Keywords: Robinson, Jackie, -- 1919-1972 -- Fiction; Robinson, Jackie, -- 1919-1972 -- Fiction; Satlow, Steve -- Fiction; Baseball -- Fiction; African Americans -- Fiction; Jews -- Fiction; Race relations -- Fiction; Prejudices -- Fiction; Friendship -- Fiction; Christmas trees -- Fiction; Baseball -- Fiction; African Americans -- Fiction; Jews -- United States -- Fiction; Race relations -- Fiction; Prejudices -- Fiction; Friendship -- Fiction; Christmas trees -- Fiction; Baseball -- Fiction; African Americans -- Fiction; Jews -- United States -- Fiction; Race relations -- Fiction; Prejudices -- Fiction; Friendship -- Fiction; New York (N.Y.) -- History -- 1898-1951 -- Fiction; Historical fiction